Determinants of passengers’ satisfaction on urban rail transit in Cheras, Petaling Jaya and Subang Jaya, Malaysia. - Chong, Joe Fai; Chong, Hwei Zhen; Lim, Keng Teck; Tan, Huan Yuan (2020)
This study aimed at examining the determinants of passenger’s satisfaction with the using of five different aspects. There are five independent variables, included the service quality of urban rail transit, facilities that urban rail transit have, Safeness, diversities and psychological profile. While the dependent variable is the satisfaction towards urban rail transit. Structured self- administered questionnaire were distributed to passengers or residents among Cheras, Petaling Jaya and Subang Jaya in Malaysia using the stratified random sampling technique. A quantitative research method, with the use of questionnaire as an instrument for this research. The sum of population is 1,713,652 people in Cheras, Petaling Jaya and Subang Jaya, Malaysia. Usable responses were received from 283 passengers or residents in these 3 area, giving a response rate of 70.75 per cent. Multiple Linear Regression Analysis were performed using the Statistical Package for the Social Sciences (SPSS). The results indicate the service quality, facilities, safety and psychological profile have the significant effect on passengers’ satisfaction whereas diversities show insignificant effect on passengers’ satisfaction. Motivation to conduct this research is to prove that the rail transit is important to public and indicate public rely on rail transit rather than own transport.